Invertebrate research without ethical or regulatory oversight reduces public confidence and trust - Michael W. Brunt; Henrik Kreiberg; Marina A. G. von Keyserlingk (Humanities & Social Sciences Communications, 2022)
Abstract Ethical and regulatory oversight of research animals is focused on vertebrates and rarely includes invertebrates. Our aim was to undertake the first study to describe differences in public confidence, trust, and expectations for the oversight of scientists using animals in research. Participants were presented with one of four treatments using a 2 by 2 design; terrestrial (T; mice and grasshoppers) vs. aquatic (A; zebrafish and sea stars) and vertebrates (V; mice and zebrafish) vs. invertebrates (I; grasshoppers and sea stars). A representative sample of census-matched Canadian participants (n = 959) stated their confidence in oversight, trust in scientists and expectation of oversight for invertebrates on a 7-point Likert scale. Participants’ open-ended text reasoning for confidence and expectations of oversight were subjected to thematic analysis. Participants believed invertebrates should receive some level of oversight but at two-thirds of that currently afforded to vertebrates. Four primary themes emerged to explain participant expectation: (1) value of life, (2) animal experience, (3) participant reflection, and (4) oversight system centered. Confidence in oversight was highest for TV (mean ± SE; 4.5 ± 0.08) and AV (4.4 ± 0.08), less for TI (3.8 ± 0.10), and least for AI (3.5 ± 0.08), indicating the absence of oversight decreased public confidence. Four themes emerged to explain participant confidence, centered on: (1) animals, (2) participant reflection, (3) oversight system, and (4) science. Trust in scientists was similar for TV (4.3 ± 0.07) and AV (4.2 ± 0.07), but higher for TV compared to TI (4.1 ± 0.07) and TV and AV compared to AI (4.0 ± 0.06); absence of oversight decreased public trust in scientists. These results, provide the first evidence that the public believe invertebrates should receive some level of oversight if used for scientific experiments. The gap that exists between current and public expectations for the oversight of invertebrates may threaten the social licence to conduct scientific research on these animals.